2017
DOI: 10.1530/erc-16-0393
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of RET isoforms in medullary and papillary thyroid carcinomas

Abstract: The RET receptor tyrosine kinase mediates cell proliferation, survival and migration in embryogenesis and is implicated in the transformation and tumour progression in multiple cancers. RET is frequently mutated and constitutively activated in familial and sporadic thyroid carcinomas. As a result of alternative splicing, RET is expressed as two protein isoforms, RET9 and RET51, which differ in their unique C-terminal amino acids. These isoforms have distinct intracellular trafficking and associated signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…In recent studies, we have shown that RET51 modulates multiple critical processes that promote tumor growth and invasive spread in thyroid carcinomas [21]. In both MTC and PTC cell types, RET51 is significantly more effective than RET9 in enhancing cell proliferation, migration and anchorage-independent growth, suggesting that it may be the primary isoform contributing to tumor aggressiveness and disease progression [21]. Consistent with this, RET51 expression is correlated with increased malignancy in human thyroid tumors [21].…”
Section: Ret51 Expression Is An Indicator Of More Aggressive Diseasementioning
confidence: 64%
See 2 more Smart Citations
“…In recent studies, we have shown that RET51 modulates multiple critical processes that promote tumor growth and invasive spread in thyroid carcinomas [21]. In both MTC and PTC cell types, RET51 is significantly more effective than RET9 in enhancing cell proliferation, migration and anchorage-independent growth, suggesting that it may be the primary isoform contributing to tumor aggressiveness and disease progression [21]. Consistent with this, RET51 expression is correlated with increased malignancy in human thyroid tumors [21].…”
Section: Ret51 Expression Is An Indicator Of More Aggressive Diseasementioning
confidence: 64%
“…Despite the abundance of evidence for distinct roles of the RET isoforms, the implications of RET isoform expression in cancer, and its potential as a marker of disease course, have not been fully explored. In recent studies, we have shown that RET51 modulates multiple critical processes that promote tumor growth and invasive spread in thyroid carcinomas [21]. In both MTC and PTC cell types, RET51 is significantly more effective than RET9 in enhancing cell proliferation, migration and anchorage-independent growth, suggesting that it may be the primary isoform contributing to tumor aggressiveness and disease progression [21].…”
Section: Ret51 Expression Is An Indicator Of More Aggressive Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, treatment of an MTC cell line expressing the RET MEN2A mutant allele (TT) with sunitinib, a RET kinase inhibitor, inhibited EMT-related gene expression (Jain et al 2004b, Ameur et al 2009). RET51-and RET9-specific RET depletion in TT cells, obtained by using RNAi or a RET kinase-dead (RetKD) mutant, caused a drop in the expression of EMT transcription factors ZEB1 and TWIST1 (Lian et al 2017) and inhibited EMT-related activities (anoikis resistance, anchorage-independent growth and invasion). Moreover, this approach demonstrated that RET51 was more efficient than RET9 in sustaining EMT-related activities (Lian et al 2017).…”
Section: Desmoplastic Stromamentioning
confidence: 99%
“…1A). RET isoforms are generally coexpressed, but differ in their abilities to promote cell growth, motility and invasion (Lian et al, 2017). RET interactions with protein adaptors and signalling molecules are predominantly mediated through the key isoformspecific phosphorylated tyrosine residues pY1062 (in RET9) and pY1096 (in RET51) and a C-terminal PDZ-binding motif (FTRF 1072 in RET9 only) that lie within these isoform-specific tails (Mulligan, 2014).…”
Section: Introductionmentioning
confidence: 99%